HEALTHCARE COMMUNICATION OF 3D VISUAL TEETH OF PLAWANGAN SITE’S EARLY HUMAN SKULL - Damai, Andry Hikari; Witono, Andika; Larassati, Ratih (JURNAL SIGNAL, 2024)
Communication is part of the development of information technology for cultural health. The development of communication, such as visual communication with digitization, has rapidly discovered health issues from the history of humankind. Digitizing archaeological remains in 3 dimensions is a new technology, one of which is the model of an early human skull at the Plawangan Site. The 3-dimensional shape of the early human skull model at the Plawangan site shows pathological articulations in minor shapes, especially on the teeth, which can explain health status information. This study aims to describe the communication that can be conveyed through visual communication of the dental health status of early humans at the Plawangan Site. The research method used was descriptive qualitative with a constructivist paradigm and a 3-dimensional observational data collection technique using early human teeth at the Plawangan Site. The data analysis technique used is qualitative analysis and macroscopic analysis. From the teeth of early humans from the Plawangan Site, it can be shown that communication phenomena about maritime and agricultural activities impact dental health and are indications of dental disease. The need for survival, processed food, and limited assistive devices caused tooth decay, and molluscs and rice also indicated dietary patterns that affected the dental health of early humans at the Plawangan Site during their lifetime. Keywords: Early human teeth, Pathology, Plawangan Site, 3D visual communication, dental health